2021
DOI: 10.1177/0092055x21996784
|View full text |Cite
|
Sign up to set email alerts
|

The Syllabus Reconstructed: An Analysis of Traditional and Visual Syllabi for Information Retention and Inclusiveness

Abstract: The current research examines whether a visual syllabus aids in information retention compared to a traditional text-based syllabus. The data derive from two lower-division sociology classes, each having a different syllabus format. Utilizing a syllabus quiz during the first week of the class provides the data about whether syllabus format matters. The data suggest the visual syllabus class retained more information given that students exposed to the visual approach scored significantly higher on a quiz than t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…An opening low-stakes assignment/grade based on the syllabus can be very beneficial (Raymark & Connor-Greene, 2002). This could take the form of a mind map (McCrea & Lorenzet, 2018) or a syllabus quiz (Yarosh, 2021) that could be taken open note, multiple times. Alternatively, a 3-2-1 brief syllabus reflection can ask students to note three things they noticed or learned from the syllabus, two personal reactions (thoughts/feelings) about the syllabus, and one worry or concern.…”
Section: Discussionmentioning
confidence: 99%
“…An opening low-stakes assignment/grade based on the syllabus can be very beneficial (Raymark & Connor-Greene, 2002). This could take the form of a mind map (McCrea & Lorenzet, 2018) or a syllabus quiz (Yarosh, 2021) that could be taken open note, multiple times. Alternatively, a 3-2-1 brief syllabus reflection can ask students to note three things they noticed or learned from the syllabus, two personal reactions (thoughts/feelings) about the syllabus, and one worry or concern.…”
Section: Discussionmentioning
confidence: 99%
“…The syllabus is a gateway to any college course, and instructors have increasingly started paying more attention to both its content and purpose (Germano and Nicholls 2020; Grunert O’Brien, Millis, and Cohen 2008; Harrington and Thomas 2018; Sulik and Keys 2014). A growing body of research provides guidance on how to design a more effective syllabus, including making it more visual (Yarosh 2021), using warm and inviting language (Harnish and Bridges 2011), providing a table of contents (Atkinson and Lowney 2015), considering its length (Harrington and Gabert-Quillen 2015), and ensuring its accessibility to all students (Tincani 2004; Womack 2017). These efforts are intended to make the syllabus more welcoming and enticing to read for students (Harrington and Thomas 2018; Nusbaum, Swindell and Plemons 2021).…”
Section: Literature Reviewmentioning
confidence: 99%
“…For example, in a study conducted by Nusbaum et al (2021), students recruited from the Psychology Department's research pool at a research university who viewed a visual syllabus were more likely to perceive the professor as kinder, more approachable, and more creative as compared to students who viewed a syllabus that was more text heavy. In another study, Yarosh (2021) found that students enrolled in a Social Problem class at a midsize four-year comprehensive university who viewed a visual syllabus were more likely to score higher on a syllabus quiz as compared to students who viewed a syllabus that was more traditionally formatted as primarily a text document. In this study, images, graphs, and headings of different sizes and colors were used in the visual version of the syllabus.…”
mentioning
confidence: 97%